Energy harvesting from torsions of patterned piezoelectrics - Cha, Youngsu; You, Hangil (ACTIVE AND PASSIVE SMART STRUCTURES AND INTEGRATED SYSTEMS XII, 2018)
In this paper, we investigate the feasibility of energy harvesting from the torsions using a piezoelectric beam. The piezoelectric beam is partially patterned and is tested in an experimental setup to force pure torsional deformation. In particular, the beam consists of two identical piezoelectric parts attached on one side of a supporting substrate. We propose a model for the energy harvesting system through the equations for a slender composite beam with the physical properties and the electromechanical coupling equations of the piezoelectric material. The theoretical predictions are validated by the comparison with the experimental results.